EARLY DETECTION OF ACUTE KIDNEY INJURY IN PRETERM NEWBORNS WITH PERINATAL ASPHYXIA USING SERUM CYSTATIN - Hadžimuratovic, Emina; Hadžimuratović, Admir; Pokrajac, Danka; Branković, Suada; Djido, Vedran (Sanamed, 2023)
Introduction:The diagnosis of acute kidney injury (AKI) in preterm newborns with perinatal asphyxia based on increased serum creatinine (sCr) value and oliguria/anuria is usually delayed. The Aim of this paper is to evaluate serum cystatin C as an early predictor of AKI. Materials and methods:The study included 42 preterm newborns (24-37 weeks) with perinatal asphyxia (Apgar score (AS) ≤ 3 at 5 minutes of life or blood pH on admission ≤ 7.00). The sCr and sCys-C levels were measured on the 1st, 3rd, and 7th day of life. According to KDIGO criteria, the newborns were classified into groups, and sCr and sCys-C values were compared. Results:The mean gestational age was 29.9 ± 3.0 weeks. AKI was diagnosed in 62.8 % of patients. Of these patients, 81.5% belonged to AKI 1 group, and 18.5 % to AKI 2 group.No newborns had the criteria for AKI 3. On day 7 the mean sCr values were significantly higher in AKI (65.4± 21.8) compared with the non-AKI group (168.4±38.2) (p<0.001), but not on day 1 and 3 (p = 0.322, 0.012, respectively). The sCys-C values were significantly higher in the AKI group on day 3 ( AKI vs. non-AKI group, 0.69 ±0.22 vs. 1.22 ±0.20; p <0.001) and day 7 (AKI vs. non-AKI group, 0.62 ±0.41 vs. 1.68 ±0.20; p <0.001). The sCys-C was also an earlier marker of a more severe stage of AKI than sCr. Conclusion:The sCys-C was elevated earlier than sCr, making it a valuable diagnostic tool for AKI in preterm newborns.